Collective Action Clauses and the Restructuring of Sovereign Debt. - Kenadjian, Patrick S. (Institute for law and finance series., 2013)
The volume is a collection of articles based on presentations given at a conference on Collective Action Clauses and the Restructuring of Sovereign Debt hosted by the Institute for Law and Finance on October 27, 2011. It is supplemented by appendices containing relevant materials on collective action clauses.